Implementasi Sistem Just in Time (JIT) dalam Meningkatkan Produktivitas Perusahaan pada PT. Langgeng Makmur Utama Bangsalsari Jember - Nur Ika Mauliyah; nur qomariyah (Jurnal Akuntansi dan Audit Syariah)
Just In Time is a model where companies only produce on demand without taking advantage of available inventory and without bearing inventory costs. Production will not occur until there is a signal from the next process that indicates a production request. Productivity is the ability of every individual, system or company to produce what they want by using resources effectively and efficiently and producing the highest possible goods and services. The purpose of this study was to determine the application of the just in time method at PT. Langgeng Makmur Utama and to find out the impact of applying the just in time method on the productivity of PT. Langgeng Makmur Utama. This research uses a qualitative approach, and the type of research is descriptive. By using data collection techniques, namely observation, interviews, and documentation. The selection of subjects used a purposive technique, the validity of the data used a triangulation technique. The research results show that: 1) the management of PT. Langgeng Makmur Utama has implemented the just in time method proven by eliminating some activities that do not add value which are considered waste such as over production, waiting time, transportation, processing, inventory levels, work movements and defective goods. 2) application of the just in time method at PT. Langgeng Makmur Utama, although not yet maximized, has been able to increase the productivity of the company, as evidenced by cost savings, cost control, increased profits, price competition, good delivery performance and improved quality. So that by implementing this just in time system, the company can increase its productivity which will make the company able to survive and be competitive in this globalization era.